The Advantages of Vascularized Fibular Bone Graft For Mandibular Tumor Reconstruction - Atmodiwirjo, Parintosa; Putri, Nandita Melati (Lingkar Studi Bedah Plastik Foundation, 2012)
Mandibular reconstruction are often indicated in patient who underwent ablation or excision of the mandible due to malignancy of the oral cavity.In this paper we will discuss about the mandibular reconstruction with use of alloplastic implant, and vascularized bone graft. Four cases of oral cavity tumor which were referred to the plastic surgery division at Cipto Mangunkusumo hospital during 2005-2011, after being diagnosed with oral cavity tumor were re-viewed. Mandibular reconstruction can be done using alloplastic implant, non-vascularized bone graft or vascularized bone graft. In this paper we studied four patients who needed mandibular reconstruction after ablation of oral cavity tumors. Patients who underwent reconstruction with alloplastic implants all had complications such as broken hardware. Where as in patient who underwent free fibular tissue transfer there were no complications at all. We can conclude that in less vascularized surrounding tissue as in cases that received or will receive other treatment such as chemotherapy or radiation that vascularized bone graft are superior. The bone healing in vascularized bone graft also does not depend on creeping substitution like in non vascularized bone graft.